Demographic Characteristics of Children with Biliary Atresia in dr. Kariadi General Hospital, Semarang - Ninung RD Kusumawati; Ratna S Ritonga; Christian Kevin; Sherynne Sulaiman; Silviani S Siahaan; Juwita Pratiwi (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2022)
Background: Biliary atresia (BA) is a progressive fibrosing obstructive cholangiopathy involving both the intrahepatic and extrahepatic biliary system; resulting in obstruction of bile flow and neonatal jaundice. Early diagnosis of biliary atresia and Kasai procedure improves patients outcome. Data form several studies revealed that BA is the most common cause of neonatal cholestasis (25%) and the leading cause of end-stage liver disease in pediatric population. The aim of this study is to determine the outcome and characteristics of children with biliary atresia in dr. Kariadi General Hospital, Semarang. Methods: In this study, a retrospective database analysis of 80 infants diagnosed with biliary atresia was conducted. Patient’s demographic data including age, sex, age at disease onset, were collected from year 2018 to 2022; including all comorbidities and complications. Data regarding procedure performed for each patient and their outcome were included in this study. Results: Eighty children were included in this study. The mean age of children referred with biliary atresia was 1.89 month, while the mean age at diagnosis was 2.5 month. Most of the patients were girls. The incidence of cytomegalovirus infection comorbidity in patients with biliary atresia is quite high, which were reported at 82%. Children diagnosed with biliary atresia and cytomegalovirus infection resulted in worse prognosis than those without. Conclusion: Our study support the theories that biliary atresia may be caused by the exposure of external environment during perinatal period such as viral infection. The prognosis of patients with cytomegalovirus comorbidity is worse than that without.